Practical Precooling Methods for Alleviating Heat Strain during Occupational Heat Exposure - Wijayanto, Titis; Huda, Listiani Nurul; Rizalmi, Sigit Rahmat (Journal of Engineering and Technological Sciences, 2025)
Working in hot and humid environments poses significant challenges to thermoregulation and potentially affects performance and health. Strategies for mitigating heat stress are critical for workers exposed to high thermal loads. This study investigated practical cooling strategies, that is, phase-change vest (PCV) cooling and crushed ice (ICE) ingestion, before a physical activity in a hot and humid environment to alleviate heat strain. Two experiments were conducted to evaluate the efficacy of the cooling methods: the first experiment involved participants wearing a PCV for precooling, and the second experiment involved participants consuming an ICE (7.5 g/kg body mass) before exercising under the same conditions. Physiological responses including tympanic temperature, skin temperature, and heart rate, along with perceptual measures such as thermal sensation and perceived exertion, were assessed. The results showed that both the PCV and ICE interventions effectively reduced heat strain, although they had different effects. PCV cooling effectively reduces physiological and perceptual strains immediately after physical exertion; however, this effect does not last in the recovery phase. In contrast, ICE ingestion reliably lessens physiological and perceptual strains throughout the activity and recovery periods, substantially impacting both physical strain and the perception of effort. These findings highlight the significance of ICE ingestion as an effective strategy for enhancing worker health and safety in demanding thermal environments.